Exploring Teachers’ Understanding of Play-Based Learning and Its Integration in Practice in Public Kindergartens in Azerbaijan - Baylarova, Zeynab (My University, 2026)
This is a qualitative study that explored public kindergarten teachers’ perceptions of play-based learning and integration of it into practice. Play is emphasized in early childhood education as a part of children’s development. Although the National Preschool Education Curriculum of Azerbaijan (2022) highlights the importance of play in children’s pedagogy and holistic development, there are limited local studies on teachers’ understanding of play and experiences of it in real classrooms. This study explored two research questions: (1) How do public kindergarten teachers in Baku understand play-based learning? (2) How do public kindergarten teachers in Baku integrate play-based learning in classroom practices? In this study, 9 in-service female public kindergarten teachers participated in semi-structured interviews, and an inductive thematic approach was used in the data analysis. The findings presented that while all participants uniformly recognized the value of play in children’s development, their understandings vary from pedagogical frameworks (active, sensory activity) to narrow, activity-focused views. In terms of integration, play is used as a core part of daily classroom activities and subject learning instead of being an isolated activity. Teacher roles are mainly described as facilitators and co-participants who are actively involved in the process of play, join children during play, scaffold children’s development, and clearly do not accept traditional and passive Soviet-era models. Main influencing factors include challenges, such as neurodivergent needs and limited resources. In contrast, parents’ alignment with teachers for reviewing the gained knowledge with children at home, and teachers creating their own materials, are included in the supportive factor of integration. Additionally, the findings of the study suggested a new model called The Teachers’ Understanding and Integration Model of Play-Based Learning, describing the mutual influence between teacher cognition and integration, at the same time, how contextual factors (supportive and challenging conditions) influence the integration of play into daily practice. Proposed implications are a need for training programs, improved availability of resources, and pedagogical guidance for teachers to support the pedagogical value of play and effective integration of play-based learning in the classroom.
Keywords: Early childhood education; Play-based learning; Child development; Preschool education; Educational innovations; Teacher cognition; Classroom management; Qualitative research